A new diterpenoid from the leaves of Phyllanthus acidus. Issue 2 (17th January 2022) - Duong, Thuc-Huy; Trung, Nguyen Tien; Phan, Cam-Tu Dang; Nguyen, Vu-Duy; Nguyen, Hoang-Chuong; Dao, Thi-Bich-Ngoc; Mai, Dinh-Tri; Niamnont, Nakorn; Tran, Thi-Ngoc-Mai; Sichaem, Jirapast
Abstract: A new diterpenoid, phyllane C (1 ), along with three known compounds, ovoideal E (2 ), spruceanol (3 ), and fluacinoid B (4 ) were isolated from the leaves of Phyllanthus acidus growing in Thailand. The structures were determined by analysis of their MS and NMR data as well as by comparison with literature values. DFT-NMR chemical shift calculations and subsequent DP4/DP4+ probability methods were applied to define the relative configuration of 1 . Compound 3 showed a weak cytotoxicity against K562 cell line (IC50 41.9 ± 2.31 µg/mL). Graphical Abstract: UF0001